PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP RETURN ON ASSET PADA PT. UNILEVER INDONESIA, Tbk - Zulkhaidah; Nurul Huda (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
This study aims to analyze the effect of accounts receivable turnover and inventory turnover on return on assets simultaneously and partially. This type of research is associative. The population in this study is financial statement data in the form of balance sheet and profit and loss at Pt. Unilever Indonesia, Tbk, 1982 - 2019 (37 years) since the company went public. The sampling technique used was purposive sampling with the criteria of financial report data available for 10 consecutive years, from 2010-2019. The data analysis technique used is multiple linear regression. The results showed that accounts receivable turnover partially did not have a significant effect on return on assets. and inventory turnover has a significant effect on return on assets. while accounts receivable turnover and inventory turnover simultaneously have a significant effect on return on assets at Pt. Unilever Indonesia, Tbk.